BERPIKIR KRITIS DAN KREATIF : TERAPANNYA DALAM PEMBELAJARAN - I G. A. K. Wardani (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2006)
Critical and creative thinking skill has an important role in making decision or taking position toward something. In order to live a better life during the globalization era, every body needs to master this skill. Therefore, schools should integrate the development of this skill in their program. While critical thinking is defined as the ability to analyze information for certain purposes, creative thinking is defined as the ability to generate ideas that is rarely thought by other people. In order to be able to integrate critical and creative thinking into teaching, a teacher should: (1) become a model of critical and creative thinker, (2) be open minded, commited, and sensitive to student ability, and (3) master various techniques and strategies to encourage students to be critical and creative thinkers.